Témoignage d’une restauratrice de peintures - Véronique Sorano-Stedman (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Historically in France, conservation-restoration has sought its identity and function in institutions. What therefore is the place of conservator-restorers?  What are their profiles, skills and challenges and what is their role in the preservation of culture heritage and the emerging professional future? By their artistic sensitivity and interest in materials they resemble the painters of the past, who were also the first to restore the works of their masters. Today however, the ideal restorer must have artistic skills devoid of any hint of self-expression. From apprenticeship to scientific training, from workshops to institutes, it has always been essential to put theory into practice to make it effective and avoid misunderstandings. conservation, restauration, formation, science, esthétique, atelier